Researching Heat Treatment Process of Seed Brutes on The Experimental Plant (Eurasian Research Bulletin, 2022)
The article presents the main factors influencing the process of heat treatment of cottonseed oil, which are the heat flux density, radiation wavelength, the thickness of the layer of the processed material and the duration of processing, studied on an experimental setup.